EVALUATION OF SEAWORTHINESS OF THE TRADITIONAL LONGBOAT IN TECHNICAL ASPECTS BASED ON MODELING AND SIMULATION: EVALUASI KELAIK LAUTAN PERAHU TRADISIONAL LONGBOAT DALAM ASPEK TEKNIS BERDASARKAN PEMODELAN DAN SIMULASI - Andie Murtono; Ahmad Ilham Ramadhani; Heru Santoso; Ahmad Tubagus Tsani Risqi Aji; Muhammad Zainul Arifin; Louis Andre Ginto (Fakultas Perikanan dan Ilmu Kelautan, IPB University, 2026)
Traditional longboat fishing vessels have changed in model and shape due to fishing techniques. This research aims to evaluate the technical seaworthiness of longboats in planning fishing operations based on the results of vessel models according to the original shape. The technical evaluation includes observation, modeling, and simulation of operations at speeds of 4, 8, 12, and 16 knots on Maxsurf, and calculation of load and fuel. The results of the technical evaluation of the observations show that the longboat has been modified using Fiber-Reinforced Plastic (FRP) techniques. The vessel features a pointed bow, a flat stern, a sharp V-shaped bottom, and no outriggers. The results of the main dimension modeling were LoA 10.25 m, LwL 8.97 m; width 1.29 m; height 0.68 m; and draft 0.2 m, corresponding to the main measurement range from the observation results. The hydrostatic displacement value is 1.34 tons, the draft and immersion are 0.2 m, and the waterline height is along LwL. The operational simulations showed the estimated resistance and engine power (362.4 N; 1.25 HP), (1449.79 N; 10.02 HP), (2899.24 N; 30.02 HP), and (3528.56 N; 48.68 HP) at speeds of 4, 8, 12, and 16 knots, respectively. The total operational load was 1.29 tons, remaining below the displacement limit. Fuel consumption rates were estimated at 0.51, 4.14, 12.12, and 19.58 liters/hour at 4, 8, 12, and 16 knots, respectively. The technical aspects that have been obtained can be used as a reference for seaworthy planning in fishing operations.